Cassia auriculata capsules / Samara Yahya Kraidi … [et al.] - Yahya Kraidi, Samara; Adam, Aishah; Suratman, Nur Suraya Adina; John, Cini Mathew (Research Innovation Business Unit, 2014)
Liver cancer is one of the most common causes of cancer related death in the world; it is formed by either the liver itself or from structures within the liver, including blood vessels or the bile ducts. Many factors can contribute to induce cancer, including free radicals, which are one of the important factors involved in causing various types of cancer by causing DNA damage, and modulating gene expression of proto-oncogenes and tumour suppressor genes. Cassia auriculata Capsules is a promising product formulated with polyphenols from the finest grade of cassia auriculata flowers which prevent free radical induced tissue damage by preventing the formation of radicals, scavenging them or by promoting their decomposition and also it up regulated the tumour suppressor gene and other genes related to apoptosis machinery. Many studies have indicated the relationship between polyphenol intake and reduced risk of certain cancers, beyond its rich content of antioxidant, it also decreases the levels of total cholesterol, triglyceride, low density lipoprotein-cholesterol levels and increased the high density lipoprotein in the blood which might enhanced because of the disruption of liver function. In addition, the current used treatments for cancer such as chemotherapy, surgical and radiation has provided significant survival benefits for patients with cancer. However, it is associated with significant normal tissue toxicity, highlighting the need for therapeutic strategies that target tumour cells without compromising normal tissue function. In addition, serious side effects have associated with chemotherapy drugs such as haematological toxicities, deadening of sensory nerves (peripheral neuropathy), and hair loss adverse cardiac effect. This product showed very promising results in vitro studies by displayed specific antiproliferative effect against liver cancer cells, elicited minimal cytotoxic effect against embryonic normal liver. Thus it is killing or slowing the growth of fast growing cells and it may help to kill the remaining of cancer cells after surgery. in addition, one of the disadvantage of current chemotherapy treatment used, it might induce necrosis rather than apoptosis, which is unwanted processes marked by cellular swelling which eventually leading to cellular and nuclear lysis with subsequent inflammation. Cassia auriculata capsules markedly induced apoptosis by up regulation of p53 gene which play an important role in inducing apoptosis, Bax- pro apoptotic and caspase-3 and down regulation of Bcl-2 gene which is known as anti-apoptotic gene. Thus, this product provides a blend of many effects by it abundant content of polyphenol, decrease triglyceride and cholesterol levels, hepatoprotective effect, induce apoptosis markedly and up-regulated its related genes. All these findings suggest that Cassia auriculata Capsules might be a promising adjuvant therapy for liver cancer to reduce symptoms and to enrich and promote excellent quality of life.